The Moral Development of The Child: An Integrated Model - Hing Keung eMa (Frontiers Media S.A., 2013)
Previous theories of moral development such as those by Piaget and Kohlberg usually focused on the cognitive or rational aspect, and seldom included the affective aspect in their construction. The characteristics of the stages of moral development in the present paper are elaborated with special reference to psychological needs, altruism and human relationships, and justice reasoning. The three stages are: (1) Physical Survival, Selfishness and Obedience, (2) Love Needs, Reciprocal Altruism and Instrumental Purpose; and (3) Belongingness Needs, Primary Group Altruism and Mutual Interpersonal Expectations. At Stage 1, a deep and profound attachment to parents, empathy toward the significant others, and obedience to authorities all contribute to the physical survival of a person at this stage. People at Stage 2 are self-protective, dominant, exploitative and opportunistic. The need to love and to be loved is gratified on the basis of reciprocal altruism. People at Stage 3 have a strong desire to gratify their belongingness needs to a primary group. They are willing to sacrifice for the benefits of the group at great cost. While the psychological needs and altruism are related to the affective aspect of moral development, the justice reasoning is related to the cognitive aspect. The proposed theoretical model attempts to integrate the affective and cognitive aspects of moral development, and prototypic responses to questions related to hypothetical moral dilemmas are presented to substantiate the proposed stage structures. It is hypothesized that the sequence of these three stages is invariant of person and culture.